Musculoskeletal pain and exercise - challenging existing paradigms and introducing new: an educational review - Smith, Benjamin E.; Hendrick, Paul; Bateman, Marcus; Holden, Sinead; Littlewood, Chris; Smith, Toby O.; Logan, Pip (BMJ Publishing Group, 2018)
Traditional pain models that describe tissue pathology as a source of nocioceptive input directly linked with pain expression, have been insufficient for assessing and treating musculoskeletal pain. The need for pain to be avoided or alleviated as much as possible during physical activity has recently been challenged, with a paradigm shift from traditional biomedical models of pain towards a biopsychosocial model of pain. The aim of the review is to provide an understanding on the potential mechanisms behind exercise, and to build on this into discussing the additional theoretical mechanisms of painful exercises. Central and peripheral pain mechanisms, the immune system and affective aspects of pain are described. This review focuses on these three mechanisms as these systems appear to respond differently to painful stimulus, compared with necessitating pain-free exercises. They are discussed in relation to the biological effect of exercise for people with chronic pain, with a broader overview of possible mechanisms behind the potentially additional beneficial effect of allowing painful exercises for individuals with chronic musculoskeletal pain. This additional mechanistic consideration could be used to help clinicians in the prescription of therapeutic exercise and for researchers to advance knowledge for such a globally burdensome condition.